PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING BERBASIS MEDIA TERHADAP KEMAMPUAN KOGNITIF SISWA KELAS X SMA NEGERI 1 KEBAKKRAMAT TAHUN PELAJARAN 2010/2011 - Damayanti, Reni; Muzayyinah, Muzayyinah; Karyanto, Puguh (P Biologi FKIP UNS Surakarta, 2011)
ABSTRACT ? This research aims to find out the effect of the implementation of Contextual Teaching and Learning approach based media towards students cognitive achievement of the class X at SMA Negeri 1 Kebakkramat. This study is a quasi-experimental studies which use Randomized Control Only Design. The independent variable in this research is the application of Contextual Teaching and Learning approach based media whereas the dependent variable is students cognitive achievement. Research population is all of students on class X at SMA Negeri 1 Kebakkramat in academic year 2010/2011. The samples are taken towards class X-2 as control group and class X-3 as treatment group. The sample is taken by using Cluster Random Sampling method. The data are collected by using test. The obtained data are analyzed by using t-test. The result shows that implementation Contextual Teaching and Learning approach based media has taken good effect toward students cognitive achievement in X at SMA Negeri 1 Kebakkramat. Keywords: Contextual Teaching and Learning Approach, Learning Media, Cognitive Achievement